Peningkatan Kapasitas Perempuan Melalui Pelatihan Pengolahan Pangan Lokal Sagu di Kabupaten Kolaka Timur - Nursalam Nursalam; Helviani, Helviani; Agusriyadin Agusriyadin; Tamrin Tamrin; Ansharullah Ansharullah; Aan Wilhan Juliatmaja; Muh. Obi Kasmin; Yuli Purbaningsih; Muhtar Amin; Musadia Afa (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
One of the local food potentials in the Woitombo Village area, Mowewe District, East Kolaka Regency is the sago plant. Opportunities for utilizing local sago food processing in this area are still lacking, while the potential for this processing can support food security and nutritious eating programs in the area. The lack of knowledge and skills of the local community is the cause of not utilizing the local food potential of sago. Based on this, the service team will provide training and assistance to women who are members of a Dasawisma group, with the aim of increasing women's capacity through processing local sago food in the area using the socialization, counseling and training stages in local sago food processing, which can support the sustainable development of sago plants in supporting food security and nutritious eating programs in the area. The result of this activity is that the women who took part in the activity gained knowledge and skills in processing local sago food, with a very enthusiastic attitude in the activity and at the end of the training activity were able to make and produce local sago food preparations, namely processing wet sago into sago flour and then processing the sago flour into sinonggi (a traditional specialty food) and sago plates (traditional cakes).